Implementation of the project based learning model (PJBL) to improve learning outcomes (PJOK) football material big football games basic passing techniques - Bagus Ade Prasetia Dinata; I Made Satyawan; Made Agus Wijaya (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This research aims to determine the improvement in learning outcomes (PJOK) through material on basic football passing techniques for Class VII D students at SMP Negeri 2 Kediri by implementing the Project Based Learning learning model. This research is a type of classroom action research. The subjects of this research were students in class VII D of SMP Negeri 2 Kediri, while the object of research was material on basic passing techniques in the game of football with the implementation of the Project Based Learning learning model. Data was taken by observing tests on basic passing techniques using the inside of the foot, basic passing techniques using the outside of the foot in cognitive aspects and psychomotor aspects. Data were analyzed using Descriptive Statistics analysis. The research results show that the implementation of the Project Based Learning learning model can improve learning outcomes (PJOK) through material on basic football passing techniques for Class VII D students at SMP Negeri 2 Kediri for the 2023/2024 academic year. It can be seen in cycle I and cycle II that the percentage increase in learning outcomes in the knowledge aspect from completeness of 7 people (21.2%) to completeness of 27 people (81.9%), increase in learning outcomes in the skills aspect from completeness of 4 people (12.2%) to 29 people (87.9%).